ANALYSIS OF RECEIVABLES MANAGEMENT SYSTEM AT BALO’ TORAJA SAVINGS AND LOAN COOPERATIVE SESEAN BRANCH - Somba, Inda Sartika; Jaya, Amir; Mongan, Claudio Julio (Indonesian Journal Of Economy Studies, 2024)
This research aims to analyze the accounts receivable management system at the Balo' Toraja Savings and Loans Cooperative (KSP) Sesean Branch. Effective accounts receivable management is crucial for the sustainability and financial health of the cooperative. This study employs a qualitative descriptive method with a case study approach. Data were collected through interviews, observations, and analysis of relevant documents. The results indicate that the Balo' Toraja KSP Sesean Branch has implemented several procedures in accounts receivable management, but there are still some weaknesses that need to be addressed. This study recommends several improvements to enhance the effectiveness of accounts receivable management at the Balo' Toraja KSP Sesean Branch.Keyword: Accounts receivable management ,Savings and loans, cooperative,System analysis, Case study, Balo' Toraja KSP Sesean Branch